A Linguistic Study of Code-Switching in Retno Marsudi’s Instagram Captions - Ni Luh Seri Wangi; Putu Devi Maharani (RETORIKA: Jurnal Ilmu Bahasa, 2026)
Code-switching has emerged as a prominent linguistic phenomenon in today’s digital communication, especially among public figures aiming to engage diverse audiences. However, few studies have explored code-switching within the context of political and diplomatic communication on social media platforms. This study aims to analyze the types and functions of code-switching found in diplomacy-themed Instagram captions posted by Indonesia’s Minister of Foreign Affairs, Retno Marsudi. A descriptive qualitative method was applied, using Poplack’s theory (as cited in Romaine, 1995) to identify the types of code-switching, and Leech’s (1974) theory to analyze their communicative functions. The data consisted of Instagram captions published between January and December 2024. The findings revealed that inter-sentential code-switching was the most dominant type (91.67%), followed by intra-sentential code-switching (8.33%), with no instances of tag-switching. In terms of language functions, the captions often served expressive, informative, and directive purposes. These results indicate that code-switching was not used randomly but rather as a deliberate strategy to reach both domestic and international audiences, combining a formal diplomatic tone with personal engagement. Overall, this study contributes to a better understanding of multilingual strategies in digital diplomacy and highlights the intentional use of code-switching in constructing political image and facilitating global communication.